Your guide to not getting murdered in a quaint English village - Johnson, Maureen, 1973- (Ten Speed Press, 2021)
"In the England of murder mysteries and TV detectives, no destination is deadlier than a quaint country village, and you never know you're in a murder village until it's too late. No attraction or local character is safe--whether in the pub for a pint, or on the manicured grounds of the local estate for a shooting party, bodies can turn up anywhere! Danger lurks around every cobblestone corner. If you are foolish enough to make the trip, at least be prepared. Brought to life with dozens of Gorey-esque illustrations by Jay Cooper and peppered with allusions to classic crime series and unmistakably British murder lore, Your Guide to Not Getting Murdered in a Quaint English Village gives you the tools you need to avoid the same fate, should you find yourself in a suspiciously cozy English village (or simply dream of going). Good luck, and whatever you do, avoid the vicar and don't drink the tea"--